The concept of human personality al-Ghazali and sigmund freud in counseling perspectives - Thahir, Andi; Hidayat, Riyan (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
The counseling perspective has a role in providing a personality description that feels needs attention in counseling. Personality, according to two figures in the science of counseling, the concept of personality formulated by Al-Ghazali and Sigmund Freud has suitability as well as facilitating or contributing personality theories to counseling that makes justification when the counseling process. The design of this study is an analytic design aimed at testing hypotheses and carrying out a more in-depth interpretation of a relationship of conformity in content and data. The difference in human concepts, according to Al-Ghazali and Sigmund Freud, lies in the workings of the three terms of human personality. Al-Ghazali explained that the dimension of the nafs is a level that has the potential that every human being will be in it. Whereas the concept of the structure of the human personality that has been explained according to Freud, that is, the three systems are interrelated and controlled by the ego as a controller for deciding a human behavior and personality.